Mana: a history of a western category - Meylan, Nicolas (Supplements of method & theory in the study of religion, 2017)
The first century of mana -- Bringing mana within theory, 1878-1904 -- The domestication of mana -- Mana in the North -- The physics of mana : from substance to unit -- Energy for a new paganism